Second International Conference on Medicine and Tennis. Case histories of wrist injuries - Weeks, P. (1997)
The Second International Conference on Medicine and Tennis was held in Paris on 31 May 1997, in conjunction with the Roland Garros tournament. Organised under the auspices of the French Tennis Federation, the conference covered the latest research in many different areas of tennis medicine. Dr. P. Weeks reviewed four case histories of tennis players who were successfully treated for wrist injuries: - TFCC rupture from the distal ulna - Scapholunate ligament disruption - Ulnar-sided wrist pain - Radius and ulna fracture, with growth arrest